Pembentukan Karakter Mandiri Siswa Melalui Sistim Boarding School Di Man Insan Cendikia Bengkulu Tengah - Ani Aryati; Qolbi Khoiri (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This research aims to determine the implementation of activities, related factors and what effective models can be applied in forming the independent character of students in the boarding school education system in Madrasah Aliyah Negeri Insan Cendikia, Central Bengkulu. The research method used by researchers is to describe the data obtained in the form of documents or qualitative writings. In this study, researchers became a key factor in obtaining data qualitative so that the data obtained can be accounted for methodologically in order to obtain data. Researchers make students, teachers and boarding supervisors a source of data. The results showed that an effective model in character building in Madrasah Aliyah Negeri Insan Cendikia Bengkulu Tengah is an integration model correlational, connecting the knowledge, understanding and practice of the values of character obtained with social reality during society